Transthoracic M-mode echocardiographic assessment of pulmonary vein-to-pulmonary artery ratio in healthy horses - Caivano, Domenico (PLoS One, 2019)
Equine cardiovascular structures and function are routinely assessed by transthoracic echocardiography. Recently, investigators have described the echocardiographic visualization of equine pulmonary vein ostia. In companion animals, the right pulmonary vein (RPV) to right pulmonary artery (RPA) ratio has been used as an index to estimate the severity of cardiac diseases resulting in left ventricular volume overload. We sought to assess the feasibility of measuring RPV and RPA dimensions, and sought to provide various previously examined RPV and RPA variables in clinically healthy horses that could be used to assess cardiopulmonary disease status. Echocardiographic examination was prospectively performed in 70 healthy horses. The RPV and RPA were visualized using a modified right parasternal long-axis view and maximum and minimum diameters of both vessels were measured from 2D guided M-mode traces. The aortic diameter (Ao) was measured from the right parasternal short-axis view in early diastole. These measurements were then used to produce various ratio indices. RPV and RPA were imaged in all 70 horses. Median of the minimum and maximum RPV/RPA was 0.51 and 0.60, respectively. Median fractional dimensional change of vessels was 33% for RPV and 22% for RPA. The medians of the minimum and maximum RPV/Ao and RPA/Ao were 0.18, 0.28, 0.35 and 0.46, respectively. No relationships between either bodyweight or heart rate and any of the vein or artery variables were identified (maximum r(2) = 0.04). Inter- and intra-observer measurement variability was very good for all RPV and RPA measurements. Measuring of RPV and RPA diameters using M-mode transthoracic echocardiography is feasible in healthy horses. Further studies of these variables in horses with cardiac diseases are needed to determine the clinical applicability and utility.